AGRICULTURAL SURPLUS PARITICIPATION IN AGRICULTURAL ECONOMIC DEVELOPMENT - Alaa M. Abdullah (Mesopotamia Journal of Agriculture)
This research interest in the subject agricultural surplus as a component of agricultural growth and its mechanisms, especially in developing countries and its contribution to agricultural development, and thus serves as an instrument for overall economic growth in much of the developing world, and the high growth of the agricultural sector is essential to stimulate overall economic growth .The problem with research that rely on agriculture for development in developing countries is still limited, many of these countries is still weak growth rates in agriculture and the shift does not mention the structure of the sector, which generates the problem of exploiting the power of agriculture for development. The research was a study following variables that can affect agricultural surpluses and thus to estimate the effects that can produce this surplus in the agricultural growth rate in three types of developing countries in 2004, sorted according to the share of agriculture to overall growth, and to answer the following question: Are we still in the can agricultural growth to give a strong impetus to overall growth in a globalizing world, and what actions are necessary to accelerate agricultural growth to fulfill its historic role, relying on the premise that positive growth rates in the past